Analisis Fenomena Heterogenous Dampak Perubahan Nilai Tukar terhadap Inflasi di ASEAN-5 - Rawang, Ashadi Asral; Ekananda, Mahjus (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
Asian’s financial crisis in 1997/1998 is a crisis that caused by exchange rate change which is contagious from one to another country. By having an active regional financial cooperation, this crisis can be prevented better. In the context of regional coordination, it is important to know the impact of exchange rate on inflation, whether it has a homogenous or heterogenous impact across ASEAN countries. By forming data panel of ASEAN-5, using broadmoney, trade openness and trading partner inflation rate as control variable with FGLS Estimator, it is known that the impact of exchange rate on Inflation in ASEAN-5 is heterogeneous.